Juridical Analysis Of Central And Regional Government Development Implementation Given Law Number 25 Of 2004 Concerning The National Development Planning System - Maria Yeti Andrias; Yulianus Payzon Aituru; Liani Sari; Sardjana Orba Manullang (IHSA Institute, 2022)
Many things happened after the collapse of the New Order government in Indonesia. Reform necessitated a change in the constitution so that, in the end, the direction of national development also changed. Where previously it was the Outlines of State Policy, now it is formulated in law through the National Development Planning System. This study aims to find out and analyze the implementation of development by the central and regional governments according to Law Number 25 of 2004 concerning the National Development Planning System. The normative research method analyzes law, legal principles, legal rules, legal systems, and various juridical concepts. The data needed in this writing is secondary data as the main data and primary data as supporting data—legal materials, namely data obtained from literature studies, archives, and library materials. The study results show that the SPPN Law is even more appropriate and follows the constitutional mandate. This law is consistent as a reference for planning. Then it accommodates guidelines for regularly planning, compiling, establishing and evaluating long and medium-term development policies. Furthermore, the basis for implementing development planning is determined by legal products that are formally regulated and stipulated by hierarchical laws and regulations.